Mutagenicity of New Lead Compounds to Treat Sickle Cell Disease Symptoms in a Salmonella/Microsome Assay - dos Santos, Jean Leandro [UNESP]; Varanda, Eliana Aparecida [UNESP]; Lima, Lidia Moreira; Chin, Chung Man [UNESP] (Mdpi Ag, 2010)
A series of phthalimide derivatives planned as drugs candidates to treat the symptoms of sickle cell anemia were evaluated in a mutagenicity test using strains of Salmonella typhimurium TA100 and TA102, without and with addition of S9 mixture, with the aim to identify the best structural requirements for a drug candidate without genotoxic activity. The compounds (1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl)methyl nitrate (1); (1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl)ethyl nitrate (2); 3-(1,3-dioxo-1,3-dihydro-2H-iso-indol-2-yl)benzyl nitrate (3); 4-(1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl)-N-hydroxy-benzenesulfonamide (4); 4-(1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl) benzyl nitrate (5) and 2-[4-(1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl)phenyl]ethyl nitrate (6) presented mutagenic potency ranging between 0-4,803 revertants/mu mol. These results allowed us to propose that a methyl spacer linked to a nitrate ester subunit associated to meta aromatic substitution decreases mutagenicity.
Keywords: AMES test; mutagenicity; sickle cell; phthalimide derivatives